The International Criminal Court and contemporary criminal law (Revista do Tribunal Regional Federal da 3ª Região, 2012)
This essay is based on a lecture given by the author at the ‘1st National Seminar on Criminal Law and Criminal Procedure in the Serrana Region’, held on 23 October 2010 in the city of Nova Friburgo. The text provides a general overview of the emergence and current state of the International Criminal Court - ICC, and then analyses its criminal procedures in the light of the main contemporary legal systems. Next, some considerations are made about the effectiveness of the ICC and possible alternative solutions for settling criminal disputes in the international arena. The aim is to encourage critical thinking about today's criminal and criminal procedure world through comparative experience
Keywords: International Criminal Court; contemporary legal systems; structure; conflict resolution; criticisms